THE HEARTH AND THE OUTSKIRTS OF THE MORAL DOMAIN: FROM BIOETHICS TO ANIMAL RIGHTS - Bartkienė, Aistė (Problemos, 2017)
This article explores the concept of caring for the other while analyzing cultural understanding about the needs and rights of the cared for. The other is considered in a very broad perspective, which includes not only humans, but also animals and other members of biotic community. Drawing on the theories of the ethics of care, it is shown how emotional dimension and attention to care practices can enrich traditional bioethical approach, while expanding its limits so as to encompass all living creatures capable of suffering. It is claimed that respectful caring for the animals and our environment is a habit, that is learned from childhood and that it is adjusted according to the prevailing values existing in particular society. The changing attitudes towards animals and environment is depicted by referring to the most significant theories in the animal ethics and environmental fields. This shift can be illustrated by B. Rollin, who claims that there is no morally relevant difference between humans and animals that justifies excluding animals from what he calls “the moral arena” or the full “scope of moral concern”. In this article it is proposed that the extension of the arena of bioethics can be made using the concept of care, offered by Noddings, so that it could embrace non-human living creatures and whole environment in its domain.